2011
DOI: 10.1136/neurintsurg-2011-010075
|View full text |Cite
|
Sign up to set email alerts
|

Direct puncture of the highest cervical segment of the internal carotid artery for treatment of an iatrogenic carotid cavernous fistula in a patient with Ehlers-Danlos syndrome: Figure 1

Abstract: A case of an iatrogenic direct carotid cavernous fistula in a patient with a history of Ehlers-Danlos syndrome and multiple aneurysms is reported. The fistula developed after unsuccessful surgical thrombectomy and revision of an occluded interposition graft inserted to treat a right internal carotid artery aneurysm. Direct puncture of the right internal carotid artery at the level of the skull base was performed to close the fistula. This case shows that direct puncture at the highest cervical segment of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Five (5.2%) patients [ 18 , 40 , 46 , 47 , 50 ] experienced a direct sCCF recurrence on the contralateral ICA 2.5 years, IQR [2.0–3.5] after the first fistula. Of 97 patients, 4 (4.1, 75.0% male) were diagnosed either with a direct CCF following minor trauma [ 7 , 11 , 14 ] or with an iatrogenic direct CCF after placement of a Fogarty balloon into the cavernous segment of the ICA [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five (5.2%) patients [ 18 , 40 , 46 , 47 , 50 ] experienced a direct sCCF recurrence on the contralateral ICA 2.5 years, IQR [2.0–3.5] after the first fistula. Of 97 patients, 4 (4.1, 75.0% male) were diagnosed either with a direct CCF following minor trauma [ 7 , 11 , 14 ] or with an iatrogenic direct CCF after placement of a Fogarty balloon into the cavernous segment of the ICA [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of 97 patients, 4 (4.1, 75.0% male) were diagnosed either with a direct CCF following minor trauma [ 7 , 11 , 14 ] or with an iatrogenic direct CCF after placement of a Fogarty balloon into the cavernous segment of the ICA [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…1 Recently, Khan et al reported successful embolization of a CCF in a patient with EDS IV by direct puncture of the highest cervical segment of the ICA after failure of a transvenous approach. 12 In addition, Hollands et al reported a case of initial surgical exposure of the ipsilateral carotid artery and internal jugular vein with placement of endovascular sheaths in lieu of a transfemoral access. 13 Our patient had a direct CCF which, in addition to the typical symptoms, was causing significant cerebral venous hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The complications are severe and include retroperitoneal hematoma, colonic rupture and iliac artery perforations 1. Recently, Khan et al reported successful embolization of a CCF in a patient with EDS IV by direct puncture of the highest cervical segment of the ICA after failure of a transvenous approach 12. In addition, Hollands et al reported a case of initial surgical exposure of the ipsilateral carotid artery and internal jugular vein with placement of endovascular sheaths in lieu of a transfemoral access 13…”
Section: Discussionmentioning
confidence: 99%